Building Walls Through Cultural Exchange: NHK’s Cool Japan and Home Sweet Tokyo - Lafontaine, Andree (Department of Communications, Universitas Islam Indonesia, 2022)
In this paper I look at two programs broadcasted on NHK—Japan’s public broadcaster—featuring foreigners living in Japan, Cool Japan and Home Sweet Tokyo, and the refracted ways in which Japanese identity is constructed through gazes that are self-Orientalizing and Occidentalizing. I place the two within three contexts: the Cool and Sugoi Japan campaigns, the foreign talent industry, and the increased concerns over foreigners in Japan. Using a functionalist approach, my analysis highlights the roles played by these two programs within Japanese society and for a Japanese audience, especially in its representation of foreign residents in light of cultural nationalism. While NHK produces some programs featuring non-Japanese hosts and guests, Cool Japan and Home Sweet Tokyo are of unique interest for their purported aim to represent and give voice to foreigners living in Japan.